Prevalence of Molar-Incisor-Hypomineralisation among school children in four German cities - Petrou, Marina Agathi; Giraki, Maria; Bissar, Abdul-Razak; Basner, Roger; Wempe, Cornelia; Altarabulsi, Mohammad Basel; Schäfer, Michael; Schiffner, Ulrich; Beikler, Thomas; Schulte, Andreas G.; Splieth, Christian H. (International journal of paediatric dentistry, 2014)
BACKGROUND: A wide range for the prevalence of Molar-Incisor-Hypomineralisation (MIH) has been found in regional studies. - AIM: The aim of this study was to determine the prevalence of MIH in Germany and to compare the findings with other studies. - DESIGN: In the compulsory dental school examination, the first permanent molars, permanent incisors, and second primary molars were examined according to EAPD criteria in 2395 children (8.1 ± 0.8 years) in four regions in Germany for the presence of MIH. Examinations were performed by five calibrated examiners (κ = 0.9) on clean teeth after toothbrushing. - RESULTS: The prevalence of MIH at the four regions differed considerably (4.3-14.6%) with a mean prevalence of 10.1%. The DMFT/dmft was generally low, but children with MIH exhibited statistically significant higher caries values. A total of 12.0% of the children with MIH also had at least one affected primary molar, which resulted in a statistically significant correlation between primary and permanent teeth. Most of the affected teeth had demarcated opacities, but more than half of the affected children showed at least one tooth with severe MIH. - CONCLUSIONS: Molar-Incisor-Hypomineralisation is a prevalent finding in German school children. The prevalence varies highly in different regions, and the high rate of severe forms has clinically relevant implications.